2020
DOI: 10.15252/embj.2019101767
|View full text |Cite|
|
Sign up to set email alerts
|

Glycolysis regulates Hedgehog signalling via the plasma membrane potential

Abstract: Changes in cell metabolism and plasma membrane potential have been linked to shifts between tissue growth and differentiation, and to developmental patterning. How such changes mediate these effects is poorly understood. Here, we use the developing wing of Drosophila to investigate the interplay between cell metabolism and a key developmental regulator—the Hedgehog (Hh) signalling pathway. We show that reducing glycolysis both lowers steady‐state levels of ATP and stabilizes Smoothened (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 87 publications
3
34
0
Order By: Relevance
“…Since Rpk and ATP α are expressed at higher levels in the cells that receive Hh, which have been postulated to make synapse‐like projections with cells that produce Hh (González‐Méndez et al, 2017), it is conceivable that these channels could modulate synapse function. Additionally, while our work was under review, it has been reported that reducing glycolysis depletes ATP levels and results in depolarization in the wing imaginal disc, reducing the uptake of Hh pathway inhibitors and stabilizing Smo at the cell membrane (Spannl et al, 2020). Importantly, all these mechanisms are not mutually exclusive and their roles in Hh signalling are avenues for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Since Rpk and ATP α are expressed at higher levels in the cells that receive Hh, which have been postulated to make synapse‐like projections with cells that produce Hh (González‐Méndez et al, 2017), it is conceivable that these channels could modulate synapse function. Additionally, while our work was under review, it has been reported that reducing glycolysis depletes ATP levels and results in depolarization in the wing imaginal disc, reducing the uptake of Hh pathway inhibitors and stabilizing Smo at the cell membrane (Spannl et al, 2020). Importantly, all these mechanisms are not mutually exclusive and their roles in Hh signalling are avenues for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Smo signalling then activates the transcription factor Cubitus interruptus (Ci) and its target genes. The work by Spannl et al (2020) demonstrates that the splicing factor Ecd directly splices several enzymes of the glycolytic pathway, GAPDH , PYK and PDK to drive glycolysis, ATP production and membrane potential via the Na + (blue)/K + (orange)‐ ATP ase pump. The sodium/potassium pump in addition to importing nutrients into the cell is also responsible for transporting a small lipoprotein ( LPP )‐associated inhibitor called N‐acylethanolamides (purple) that destabilises Smo to repress Hh signalling and maintain the correct shape of the developing wing imaginal disc.…”
Section: Figure Atp Drives Atpase Pump Membrane Potential and Hh Patmentioning
confidence: 99%
“…Notably, previous work has hinted at this connection, as inhibition of the pyruvate metabolism pathway has been linked to overgrowth phenotypes reminiscent of Notch signalling activation (Saj et al , 2010). In this issue of The EMBO Journal , Spannl et al (2020) further investigate this association, through elegant genetic studies and the use of bio‐sensors. Together, their data suggest that energy metabolism affects wing patterning, through ATP‐driven membrane import of negative regulators of the Hh signalling pathway.…”
Section: Figure Atp Drives Atpase Pump Membrane Potential and Hh Patmentioning
confidence: 99%
See 1 more Smart Citation
“…4 On longer timescales, Vmem displays diverse patterns, including responding to growth factor signals, 5,6 oscillating throughout the cell cycle, 7 and marking developmental boundaries in tissue. 3,8 Further, these voltage signals can be compartmentalized into small areas such as dendritic spines 9 or delocalized over larger tissues. 10 Accurate and non-invasive Vmem recording techniques are required to document and understand the many roles of Vmem.…”
Section: Introductionmentioning
confidence: 99%